Performance of Tuberculosis Program Officers in the Implementation of Contact Investigations in Medan City - Syafrina Ulfah; Siti Khadijah Nasution; Fazidah Aguslina Siregar (International Journal Labs, 2023)
Indonesia is the second country with the most TB cases in the world. One of the efforts to overcome TB in Indonesia is the active discovery of TB cases through contact investigations. However, the implementation of contact investigations has not been fully optimal, including in Medan City. The implementation of contact investigations still reached 14.79 percent in 2020. The performance of TB program officers is one of the factors that determine the achievement of the implementation of contact investigations. This study aims to explore the performance and factors that contribute to the performance of TB program officers in the implementation of contact investigations in Medan City. This research was qualitative research conducted from December 2022 to January 2023. The data collection method was an in-depth interview and review of documentation. The location of study was conducted at six health centers in Medan City. The research informants totaled 37 people consisting of the Deputy TB Supervisor (Wasor TB) of the Medan City Health Office, TB program officers of health centers, TB cadres, heads of health centers, laboratory analysts, doctors, TB sufferers, and drug swallowing supervisor (PMO). The results showed that the performance of TB program officers was not optimal. Factors that contributed to performance were the limited number of TB program officers at health centers, limited time from TB program officers because they had other duties, limited funds for the implementation of contact investigations, suboptimal coordination between TB program officers and cadres, and obstacles from the community who were not willing to conduct contact investigations.